COMPENSABLE FACTORS AND COMPARISON ANALYSIS OF UMP AND UMK IN TEACHER COMPENSATION SYSTEM IN JAWA BARAT - Kartika, Lindawati; Rahmawati, Siti; Eriza, Dea Nur; Ramadhoni, Refindi Rizky; Cahyaningtyas, Erri Utami (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
ABSTRACTEducation is an aspect that needs to be improved because quality human resources (HR) are born from quality education. Teachers have an important role in improving human resources, and teacher welfare also needs to be considered, one of which is by paying attention to the compensation system for teachers to match the regional minimum wage, compensable factors, and job qualifications. The purpose of this study was to evaluate compensation, especially teacher salaries, in West Java against the UMP and UMK, analyze the compensable factors of the teaching profession based on the Hay System, analyze the qualifications of teacher positions needed based on compensable factors, and compile recommendations for teacher job qualifications based on compensable factors and realization of the needs of the teaching profession in available job vacancies. This research is a quantitative descriptive study with a sample of 150 teachers from six schools in West Java, especially in the areas of Depok, Bandung, Bogor, Pangandaran, and Cirebon. The sources of data are secondary data in the form of surveys on teacher salaries in West Java and literature studies. The data analysis method used the descriptive analysis method and the hay system to determine compensable factors. The results show that the average salary of teachers in West Java is already above the regional minimum wage. There are ten compensable factors needed in determining the teacher compensation system in West Java, and education is the most important aspect with the highest weight. Several job qualifications are in accordance with the compensable factors needed in determining the teacher's compensation system, namely education, experience, communication, conceptual thinking, initiative, freedom of action, and physical effort. However, the compensable factors, complexity, decision-making, and impact are not included in the teacher's job qualifications so that these three factors can be taken into consideration to be used as job qualifications for teachers in the future.Keywords: compensable factors; compensation; Provincial Minimum Wage (UMP) and Minimum Wage of City and Districts (UMK); school